2016
DOI: 10.3766/jaaa.15126
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing as an Adjunct to Hearing Rehabilitation for Patients with Tinnitus: A Randomized Controlled Pilot Trial

Abstract: Tinnitus handicap scores decrease to a greater extent following brief MI than following SP. Future research on the value of incorporating MI into audiological rehabilitation using randomized controlled designs is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The only intervention performed with patients was the fitting of hearing aids; no tinnitus-specific counseling was provided. Patients with hearing loss and tinnitus were divided into two groups; one received a brief motivational interviewing program (including open questions, reflective listening, summaries, and affirmations) as a counseling model included in the hearing aid fitting process, and the other received standard practice (with conventional hearing rehabilitation, fine-tuning of amplification, and functional evaluation) (Zarenoe et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The only intervention performed with patients was the fitting of hearing aids; no tinnitus-specific counseling was provided. Patients with hearing loss and tinnitus were divided into two groups; one received a brief motivational interviewing program (including open questions, reflective listening, summaries, and affirmations) as a counseling model included in the hearing aid fitting process, and the other received standard practice (with conventional hearing rehabilitation, fine-tuning of amplification, and functional evaluation) (Zarenoe et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Aazh 23 was deemed to be at low risk-of-bias. Ferguson et al, 24 Zarenoe et al, 25 and the clinical trial by Lewis 26 (NCT 01843777) were at some risk-of-bias from the randomization and outcome measurement processes (►Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…In summary, out of the 16 studies described above, nine studies showed significant improvements in tinnitus perception (Araujo and Iório 2016; Cabral et al 2016; Haab et al 2019; Hodgson et al 2015; Shekhawat et al 2014; Yakunina et al 2019; Yokota et al 2020; Zarenoe et al 2017; Zarenoe et al 2016), while four studies did not report significant tinnitus relief (Marcrum et al 2020; McNeill et al 2012; Peltier et al 2012; Strauss et al 2015). The other three studies did not test whether hearing aids’ use leads to tinnitus relief (Andersson et al 2011; Shekhawat, Searchfield, Kobayashi, et al 2013; Shetty and Pottackal 2019).…”
Section: Resultsmentioning
confidence: 91%
“…It was recommended more recently to have a washout period of a few days between the stimulation sessions because the impact of multiple tDCS sessions on tinnitus being non-linear in nature (Shekhawat et al 2018). Zarenoe et al (2016) looked also into the optimization of hearing aids for tinnitus relief by adding motivational interviewing (MI) to their protocol. This pilot RCT included 50 patients with tinnitus and sensorineural hearing loss, but four patients dropped out due to dissatisfaction of hearing aid amplification.…”
Section: Resultsmentioning
confidence: 99%